Coreness of Cooperative Games with Truncated Submodular Profit Functions (2018) - Chen, Wei; Shan, Xiaohan; Sun, Xiaoming; Zhang, Jialin (2018 Algorithmic Game Theory, 2018)
Coreness represents solution concepts related to core in cooperative games, which captures the stability of players. Motivated by the scale effect in social networks, economics and other scenario, we study the coreness of cooperative game with truncated submodular profit functions. Specifically, the profit function \(f(· )\) is defined by a truncation of a submodular function \(σ (· )\): \(f(· )=σ (· )\) if \(σ (· )η \) and \(f(· )=0\) otherwise, where \(η \) is a given threshold. In this paper, we study the core and three core-related concepts of truncated submodular profit cooperative game. We first prove that whether core is empty can be decided in polynomial time and an allocation in core also can be found in polynomial time when core is not empty. When core is empty, we show hardness results and approximation algorithms for computing other core-related concepts including relative least-core value, absolute least-core value and least average dissatisfaction value.